Student Management System: A Web-Based Solution for Academic Administration (International Journal of Scientific Research in Science and Technology, 2025)
The Student Management System is a web-based application designed to efficiently manage and streamline various academic activities. It provides a centralized platform for students, teachers, and administrators to access information related to attendance, courses, feedback, and personal profiles. The system aims to eliminate the inefficiencies of traditional manual processes by offering real-time, easy-to-use features that enhance productivity and accuracy.developed using Python Django for the backend and HTML, CSS, JavaScript, Bootstrap, and Ajax for the frontend, the system ensures a smooth, responsive user experience. Administrators can manage students, staff, subjects, and feedback, while students and teachers can view and update their profiles, monitor attendance, and communicate seamlessly. By integrating modern web technologies and relational databases, the project not only simplifies academic management but also Show cases practical implementation skills in building robust, scalable web applications.